3-D resistivity imaging of the supercritical geothermal system in the Sengan geothermal region, NE Japan. (July 2022) - Yamaya, Yusuke; Suzuki, Yota; Murata, Yasuaki; Okamoto, Kyosuke; Watanabe, Norihiro; Asanuma, Hiroshi; Hase, Hideaki; Ogawa, Yasuo; Mogi, Toru; Ishizu, Keiichi; Uchida, Toshihiro
Highlights: A conductor was found in the high-temperature Quaternary Kakkonda granite. Permeability was estimated based on the resistivity distribution. A supercritical geothermal reservoir corresponds to the top of the intrusion. This is originated by heat and water supply from deep magmatic fluids. Abstract: A wideband magnetotelluric survey was performed in the Sengan geothermal region of northeastern Japan. A conductor with resistivity of < 30 Ωm was found at an elevation of -1.8 km in the Quaternary Kakkonda granite. Microseismic activity was not observed in the conductor, suggesting a ductile zone with temperatures exceeding 370 °C. Under these conditions, H2 O-NaCl fluids can exist as two-phase or single-phase types. The permeability of the upper reservoir surface is between 3.0E-17 and 5.0E-15 m 2, indicative of an exploitable supercritical geothermal reservoir. Our results indicate that this is originated by heat and fluid supply system from magma.